Central compaction in the process of lens growth as indicated by lamellar cataract. Issue 7 (July 1988) - Brown, N A; Sparrow, J M; Bron, A J
Abstract : The lens growth through life is the net result of surface accretion partially offset by central compaction. Compaction has previously been shown to affect the cortex. The present study examines compaction in the nucleus by measuring the change in dimensions of congenital lamellar cataract with time and by comparing the different dimensions of dominantly inherited lamellar cataract in individuals of different ages in the same family. It is now shown that compaction affects the nucleus at a decreasing rate with increasing age and that the rate of compaction of lamellar cataracts is faster the greater diameter of the affected lamella. It is concluded that compaction of lens fibres towards the centre of the lens affects all regions of the cortex and nucleus in youth and that the compaction becomes largely or completely confined to the cortex in middle age and beyond. The shape of the lamellar cataract changes from a lenticular shape in youth to a rounded shape with increasing age. This accounts for the development of the peripheral divergence of the zones of discontinuity of the cortex, which allows the lens to remain emmetropic with increasing age in spite of changes in surface curvature.